Surveillance Health Society: Ethics, Privicy, and Social Control in Digital Health Systems - Hendra Cipta; Isah Fitriani; Ryryn Suryaman Prana Putra (Journal of Public Health Indonesian, 2026)
The rapid expansion of digital health systems has transformed healthcare delivery while simultaneously embedding pervasive practices of surveillance within everyday life. Technologies such as electronic health records, wearable devices, and health analytics enable continuous monitoring and data-driven governance of bodies and behaviors. This study critically examines digital health systems through the lens of surveillance society, focusing on the ethical implications of privacy, autonomy, and social control. Employing a qualitative normative–critical approach, the study analyzes policy documents and academic literature from health ethics, surveillance studies, and critical social theory. The findings show that digital health systems function as infrastructures of continuous surveillance that classify risk, normalize behavior, and reshape relations between individuals, states, and technology providers. Ethical challenges arise from weakened informed consent, data commodification, and profound power asymmetries that limit individual control over personal health data. The study further argues that health-based narratives of prevention and security legitimize intrusive forms of governance, positioning digital health as a mechanism of social control rather than purely a tool of care. This research concludes that ethical governance of digital health requires moving beyond technocratic and procedural approaches toward a critical framework that addresses power, justice, and accountability in data-driven health systems